Comparison of Surgical Results in Patients With Advanced and Limited Disease With Multiple Endocrine Neoplasia Type 1 and Zollinger-Ellison Syndrome - Norton, Jeffrey A. (2001)
OBJECTIVE: To determine the role of surgery in patients with Zollinger-Ellison syndrome (ZES) and multiple endocrine neoplasia type 1 (MEN1) with either limited or advanced pancreatic endocrine tumors (PETs). SUMMARY BACKGROUND DATA: The role of surgery in patients with MEN1 and ZES is controversial. There have been numerous previous studies of surgery in patients with PETs; however, there are no prospective studies on the results of surgery in patients with advanced disease. METHODS: Eighty-one consecutive patients with MEN1 and ZES were assigned to one of four groups depending on the results of imaging studies. Group 1 (n = 17) (all PETs smaller than 2.5 cm) and group 3 (n = 8) (diffuse liver metastases) did not undergo surgery. All patients in group 2A (n = 17; single PET 2.5–6 cm [limited disease]) and group 2B (n = 31; two or more lesions, 2.5 cm in diameter or larger, or one lesion larger than 6 cm) underwent laparotomy. Tumors were preferably removed by simple enucleation, or if not feasible resection. Patients were reevaluated yearly. RESULTS: Pancreatic endocrine tumors were found in all patients at surgery, with groups 2A and 2B having 1.7 ± 0.4 and 4.8 ± 1 PETs, respectively. Further, 35% of the patients in group 2A and 88% of the patients in group 2B had multiple PETs, 53% and 84% had a pancreatic PET, 53% and 68% had a duodenal gastrinoma, 65% and 71% had lymph node metastases, and 0% and 12% had liver metastases. Of the patients in groups 2A and 2B, 24% and 58% had a distal pancreatectomy, 0% and 13% had a hepatic resection, 0% and 6% had a Whipple operation, and 53% and 68% had a duodenal resection. No patient was cured at 5 years. There were no deaths. The early complication rate, 29%, was similar for groups 2A and 2B. Mean follow-up from surgery was 6.9 ± 0.8 years, and during follow-up liver metastases developed in 6% of the patients in groups 2A and 2B. Groups 1, 2A, and 2B had similar 15-year survival rates (89–100%); they were significantly better than the survival rate for group 3 (52%). CONCLUSIONS: Almost 40% of patients with MEN1 and ZES have advanced disease without diffuse distant metastases. Despite multiple primaries and a 70% incidence of lymph node metastases, tumor can be removed with no deaths and complication rates similar to those in patients with limited disease. Further, despite previous studies showing that patients with advanced disease have decreased survival rates, in this study the patients with advanced tumor who underwent surgical resection had the same survival as patients with limited disease and patients without identifiable tumor. This suggests that surgical resection should be performed in patients with MEN1 who have ZES and advanced localized PET.